Hello, hedgehog - Buller, Laura, 1952- (New York, New York : DK Publishing, 2019)
Introduces hedgehogs, describing why they have prickly spines covering their backs, how they hibernate, and how to properly care for a hedgehog as a pet.
Includes index.
Level 2 Beginning to read
Junior Easy Read Jan 2020
RL 2
Keywords: Hedgehogs -- Juvenile literature; Readers (Publications).